2020
DOI: 10.1111/jopr.13262
|View full text |Cite|
|
Sign up to set email alerts
|

Management of an Imminent Pathological Fracture of a Fibular Neomandible Via a Minimally Invasive Approach—A Case Report

Abstract: Fibular free flap reconstruction remains the workhorse of postmandibulectomy reconstruction. Dental implantation to support a dental prosthesis is a sought-after outcome when the area of resection involves tooth-bearing zones. Chronic perisoft tissue pedicle hyperplasia with secondary infection leading to gradual bone loss is a simple complication to manage in the general population, but it becomes a serious issue in the fibula mandibular reconstruction patient in that it can lead to pathological fracture of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…They exhibited screw loosening, fracture of titanium plates, and exposure of fixation materials out of the skin or oral mucosa which would eventually ensue infection requiring complete removal of reconstructive materials [ 88 ]. Moreover, the future oral rehabilitation using dental implant usually became limited, for reinforced titanium plates were not able to provide the oral prosthesis with a supporting hard tissue table for rehabilitation of occlusion [ 89 , 90 ]. A titanium mesh structure was also suggested that presented an occlusal table for an oral prosthesis as designed with a similar dimension to the original mandible.…”
Section: Factors For Clinical Applicationmentioning
confidence: 99%
“…They exhibited screw loosening, fracture of titanium plates, and exposure of fixation materials out of the skin or oral mucosa which would eventually ensue infection requiring complete removal of reconstructive materials [ 88 ]. Moreover, the future oral rehabilitation using dental implant usually became limited, for reinforced titanium plates were not able to provide the oral prosthesis with a supporting hard tissue table for rehabilitation of occlusion [ 89 , 90 ]. A titanium mesh structure was also suggested that presented an occlusal table for an oral prosthesis as designed with a similar dimension to the original mandible.…”
Section: Factors For Clinical Applicationmentioning
confidence: 99%